PERANCANGAN BRANDING DAN APLIKASI KEMASAN PRODUK OLAHAN LIDAH BUAYA SEBAGAI PRODUK CINDERAMATA KHAS KOTA PONTIANAK - Febrina Triutari S1 (Saraswati)
This research aims to design branding and packaging application of processed aloe vera products which can show unique attributes and product values properly and aesthetically and also to promote the image of the product as unique souvenir icon from Pontianak City. Design concept that is going to be used in designing the branding and packaging application on processed aloe vera product is a concept which able to show unique attributes and product values aesthetically on its brand and packaging application. The style that want to be shown on this design are modern-looked and simple but elegant, so it has strong appeal and able to dominate the other packaging designs. The impressions that want to be shown on the product are natural, fresh and hygienic.The conclusion is this design wants to show the product illustration and the brand logo dominantly, tagline and other elements and attributes on the package. Therefore, a proper branding concept and an aesthetic packaging with unique attributes which can show product values, hopefully, able to promote product image as unique souvenir icon from Pontianak City.Keywords: Branding, Packaging, Aloe Vera, Pontianak City